Language Style On Food Advertising On The Internet - Fauziah Nur; Maria Asrani Silalahi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The language used in making advertisements must be with the right choice of words and is inviting and can influence many audiences. The language used in making advertisements must be clear, concise, concise and easy to understand. Therefore, it is necessary to choose words, language styles that are unique and attractive to attract the attention of consumers.